Considering the role of material gerontology in reimagining technology design for ageing populations - Helen Manchester; Juliane Jarke (International Journal of Ageing and Later Life, 2022)
The promise of technology to provide solutions to the global concern of ageing populations has largely been unfulfilled. We argue that this is, in part, related to design processes that fail to take account of the rich material lives of older people, and that often adopt stereotypical views of older people as frail, vulnerable and unskilled. We draw on empirical data from two co-design projects, to suggest the contributions that material gerontologists could make to design teams creating technologies for ageing populations. We suggest material gerontologists bring three key elements to interdisciplinary design teams: (1) making visible the intra-action of humans and non-humans in co-design processes; (2) reconfiguring co-design response-ably with older adults; and (3) reimagining possible outcomes of technology design. We believe that this approach can result in the design of products, services and innovations that respond better to the heterogeneous needs and life-worlds of older adults.